Circulating 25‐hydroxyvitamin D, vitamin D‐binding protein and risk of prostate cancer12. Issue 12 (27th December 2012) - Weinstein, Stephanie J.; Mondul, Alison M.; Kopp, William; Rager, Helen; Virtamo, Jarmo; Albanes, Demetrius
Abstract We recently reported a significant positive association between 25‐hydroxyvitamin D [25(OH)D], the accepted biomarker of vitamin D status, and prostate cancer risk. To further elucidate this association, we examined the influence of vitamin D‐binding protein (DBP), the primary transporter of vitamin D compounds in the circulation. Prediagnostic serum concentrations of DBP were assayed for 950 cases and 964 matched controls with existing 25(OH)D measurements within the Alpha‐Tocopherol, Beta‐Carotene Cancer Prevention Study of Finnish men. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs), and statistical tests were two sided. Serum DBP modified the association between serum 25(OH)D and prostate cancer, with higher risk for elevated 25(OH)D levels observed primarily among men having DBP concentrations above the median (OR = 1.81, 95% CI: 1.18–2.79 for highest vs. lowest quintile, p‐trend = 0.001) compared to those with DBP below the median (OR = 1.22, 95% CI: 0.81–1.84, p‐trend 0.97; p‐interaction = 0.04). Serum DBP was not associated with prostate cancer risk overall (OR = 0.96, 95% CI: 0.70–1.33 for highest vs. lowest quintile); however, high serum DBP was associated with significantly decreased risk of prostate cancer in men with lower (<median) 25(OH)D concentrations (OR = 0.59, 95% CI: 0.38–0.90 for highest vs. lowest quintile, p‐trend = 0.003) and increased risk in men with higher 25(OH)D concentrations (OR = 1.47, 95% CI: 0.98–2.20, p‐trend 0.10, p‐interaction = 0.02). Our data suggest that the primary vitamin D carrier protein, DBP, modulates the impact of vitamin D status on prostate cancer.